2016
DOI: 10.9799/ksfan.2016.29.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Life Status According to Smart Device Use of University Students in Korea

Abstract: The purpose of this study is to investigate the dietary life status according to smart device use among university students. In 2015, data was collected during a 3 month survey of the eating behaviors, lifestyles, eating habits, and use of smart devices of 550 university students, as well as their dependency on smartphones. Ultimately, 520 subjects (94.5% analysis rate) were divided into three groups based on their daily use time of smart device: low-use group (<4.7 hours, n=173), medium-use group (≥4.7 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The participants who have reduced smart device usage, were assessed to eat more regularly and at fixed times than those with high smart device users, who were assessed to overeat and consume processed foods more often. The results suggested that limiting mobile phone usage will show favorable results [15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The participants who have reduced smart device usage, were assessed to eat more regularly and at fixed times than those with high smart device users, who were assessed to overeat and consume processed foods more often. The results suggested that limiting mobile phone usage will show favorable results [15].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been performed to investigate the association/link between smartphone addictions & dietary patterns among school/college/university students. A study conducted by Sun-Hee Lim et al in 2016 [15], among the university Korean students, intention of the research was to explore the dietary behavior, lifestyle, food & beverages consumption pattern, and smartphones' usage among 550 students of university. It was an observational cross-sectional study and data was collected via survey using questionnaires.…”
Section: Types Of Outcome Measures Dietary Behaviormentioning
confidence: 99%
See 3 more Smart Citations